MENINGKATKAN HASIL BELAJAR LARI CEPAT MELALUI PENDEKATAN BERMAIN PADA SISWA KELAS V SEKOLAH DASAR NEGERI KEMIRIAN 1 : SD NEGERI KEMIRIAN 1 BONDOWOSO - EKO SRIANINGSIH (Mitra Pendidikan, 2021)
The purpose of this study was to find out how much the play approach can improve sprint learning outcomes for fifth grade students at the Kemirian 1 State Elementary School, Tamanan District, Bondowoso Regency. This research is a Classroom Action Research (CAR). According to Suwarsih Madya (2012), action research is a real-world practice intervention aimed at improving practical situations. CAR is a dynamic process, with four steps: 1). planning, 2) implementation 3). observation, and 4). reflection. In the implementation of this research is done in a participatory and collaborative. The research was conducted for several cycles, and each cycle was conducted twice face-to-face, each face-to-face taking 35 minutes. This research was conducted at the Kemirian 1 Public Elementary School (SDN) which is located at Jl. Karang Melok Kemirian Village, Tamanan District, Bondowoso Regency. The reason for choosing the research location at SD Negeri Kemirian 1 is that the researcher is a PJOK teacher at SDN Kemirian 1 so as to facilitate the process of carrying out research. This research was carried out. This research was carried out for 3 months, from September to November 2019 Data collection techniques carried out in this study were carried out through observation, questionnaires, and documentation. While the data analysis technique used is a descriptive quantitative percentage and qualitative descriptive technique Based on the results of the analysis and discussion that has been carried out, it can be concluded that the play approach can improve sprint learning in fifth grade students at SDN Kemirian 1, Tamanan District, Bondowoso Regency.